2021
DOI: 10.1021/acs.cgd.1c00728
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals Self-Assembled Silica-Nanosphere/Graphene Buffer Layer for High-Quality Gallium Nitride Growth

Abstract: In the van der Waals epitaxy of III-nitride semiconductor materials, graphene plays an increasingly important role. In this work, to improve the quality of the gallium nitride (GaN) film on sapphire, we innovatively propose a composite insertion layer of graphene/silica nanospheres (G/S-n). The G/S-n composite insertion layer successfully realizes van der Waals self-assembly for the silica nanospheres. The G/S-n buffer layer can effectively block threading dislocations during the growth of GaN materials, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…GaN layers grown on foreign substrates, such as sapphire, contain a high threading dislocation density (TDDs) ranging from 10 8 to 10 9 cm –2 . Screw and mixed type dislocations having a screw component of Burgers vector b = [0001] can promote the formation of growth spirals at the dislocation sites. , As a result, when the GaN substrate misorientation angle is close to 0° from the (0001) plane, hillocks of six-fold symmetry are observed.…”
Section: Introductionmentioning
confidence: 99%
“…GaN layers grown on foreign substrates, such as sapphire, contain a high threading dislocation density (TDDs) ranging from 10 8 to 10 9 cm –2 . Screw and mixed type dislocations having a screw component of Burgers vector b = [0001] can promote the formation of growth spirals at the dislocation sites. , As a result, when the GaN substrate misorientation angle is close to 0° from the (0001) plane, hillocks of six-fold symmetry are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Several procedures have been presented using different synthesis methods in GaN production, aiming for the reduction of crystalline mismatch between the material and substrate. On the one hand, Amano et al reported the use of an AlN film as a buffer layer for obtaining high-quality GaN films. Furthermore, the obtention of crystalline GaN was successfully accomplished by the two-step growth method, by depositing a low-temperature GaN film as a buffer layer to support the growth of the main film .…”
Section: Introductionmentioning
confidence: 99%
“…And the related research about the manufacturing of DUV-LED based on graphene is still not much. Additionally, the addition of sputtered AlN nucleation layer to assist the growth of the AlN epitaxial layer on the sapphire substrate has been proposed, and the research results show that the sputtered AlN layer can effectively improve the quality of the AlN epitaxial layer [36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%